2003
DOI: 10.1039/b303528j
|View full text |Cite
|
Sign up to set email alerts
|

Mass discrimination in dynamic reaction cell (DRC)-ICP-mass spectrometry

Abstract: The possibility of overcoming spectral interferences by means of selective ion-molecule chemistry in a dynamic reaction cell (DRC) leads to an extension of the application range of ICP-MS for isotopic analysis. In this work, the effect of various instrumental parameters and the matrix composition on the mass discrimination (defined as the deviation between the experimental result and the corresponding 'true' isotopic ratio) was systematically studied. It is demonstrated that various DRC parameters-collision ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 28 publications
4
38
0
Order By: Relevance
“…Severe mass discrimination has been reported in collision/reaction cells (Vanhaecke et al, 2003(Vanhaecke et al, , 2002Boulyga and Becker, 2001), but as no certified values of 135 Cs/ 137 Cs exist, no mass bias corrections were made in this work. Comparison of a standard determined with and without introduction of CH 3 Cl into the reaction cell showed no significant difference in mass bias (Taylor et al, submitted for publication).…”
Section: Mass Discriminationmentioning
confidence: 87%
“…Severe mass discrimination has been reported in collision/reaction cells (Vanhaecke et al, 2003(Vanhaecke et al, , 2002Boulyga and Becker, 2001), but as no certified values of 135 Cs/ 137 Cs exist, no mass bias corrections were made in this work. Comparison of a standard determined with and without introduction of CH 3 Cl into the reaction cell showed no significant difference in mass bias (Taylor et al, submitted for publication).…”
Section: Mass Discriminationmentioning
confidence: 87%
“…A number of studies conducted with both quadrupole-based and multi-collector ICP-MS have shown that the instrumental mass discrimination can vary considerably with the sample matrix and that the response of two elements of similar mass to a different matrix may not be sufficiently correlated. [2][3][4][5][6] The matrix-related occurrence of spectral interferences and mass discrimination indicate that accurate and precise measurements of small differences in isotopic composition should preferably be conducted on target elements that have been chemically isolated from the sample matrix.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, the situation becomes significantly more complicated when various types of (molecular) ions interfere simultaneously with the analyte signal(s) of interest. Additionally, it was recently demonstrated that the mass discrimination is substantially affected by the conditions in the cell and that when using chemical resolution in a collision or dynamic reaction cell, the matrix composition may influence the mass discrimination to a larger extent [56].…”
Section: Chemical Resolutionmentioning
confidence: 99%